A Pragmatic Study of Speech Acts in Pamuk's The Museum of Innocence: Performing Love and Longing - Chatarini Septi Ngudi Lestari (Fakultas Ilmu Budaya Universitas 17 Agustus 1945 Surabaya, 2026)
This article examines how Orhan Pamuk's The Museum of Innocence employs language to convey love, obsession, and emotional control. This study is based on Searle's speech act framework, reinforced by pragmatic and cultural contexts. Kemal, the main character, expresses his emotions through a variety of expressive and commissive acts, particularly in his letters to Fusun, reflections, and monologues. These speech acts highlight the tension between personal desires and social expectations in late 20th-century Istanbul, functioning as linguistic acts influenced by the norms of performance culture. The study analyses in depth how expressive speech acts, such as apologies and declarations of love, and commissive speech acts, including vows and promises, are used to construct and negotiate Kemal's identity in a multicultural environment, while also conveying emotions. The results reveal how language functions as a means of emotional expression and intercultural exchange, highlighting how speech acts are deeply influenced by social hierarchy, indirectness, and politeness norms. This study emphasizes literature as a crucial channel for exploring interpersonal meaning in a globalized world, situating speech act theory within the broader context of cultural pragmatics. It provides insights into how language conveys love, loss, and longing across cultures, advancing literary pragmatics and intercultural discourse analysis.